Prevalensi dan Faktor Risiko Paramphistomiasis pada Sapi Bali di Distrik Prafi, Kabupaten Manokwari, Provinsi Papua Barat (PREVALENCE AND RISK FACTORS OF PARAMPHISTOMIASIS IN BALI CATTLE IN PRAFI DISTRICT, MANOKWARI REGENCY, WEST PAPUA PROVINCE) - Purwaningsih, Purwaningsih; Noviyanti, Noviyanti; Putra, Rizki Pratama (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Paramphistomiasis is a parasiter disease caused by an Paramphistomum sp worms infection. The disease can cause a considerable decline in livestock productivity, therefore it is catagorized as one of economic affected diseases. The aims of this research were to determine the prevalence and distribution of paramphistomiasis in Bali cattle in Prafi District of Manokwari Regency, West Papua Province; and to identify some of the risk factors that associated with the paramphistomiasis prevalence. The research was done between February and March 2016. The feces samples were taken from 369 cattles perrectal were chosen by using proportional random sampling technique at village level. A total of 127 farmer respondents were interviewed. The feces samples were examined with sedimentation test to identify the existence eggs of Paramphistomum sp. based on their morphology. The data were analyzed in univariate to obtain the prevalence by dividing the number of positive sample with the number of samples inspected multiplied by 100%. Then, bivariate analysis was performed by using chi square (c2), and odds ratio (OR). The distribution of paramphistomiasis in Bali cattle that rearing in Prafi District has prevalence value in each village: Udapi Hilir, Desay, Aimasi, and Prafi Mulya was 14.74%; 12.04%; 9.18% and 1.48% respectively. While the prevalence of paramphistomiasis in bali cattle in the Prafi District was 10.03%. Factors of rearing manajemen, such as: combined shed with calve (OR=4.525) and sources of animal feed that taken from the grounds of the house and rice land (OR=4.955) showed a significant influence (P<0.05) on the risk of paramphistomiasis infection.